2012
DOI: 10.2105/ajph.2011.300349
|View full text |Cite
|
Sign up to set email alerts
|

Racial and Ethnic Disparities in Depression Care in Community-Dwelling Elderly in the United States

Abstract: Among elderly Medicare beneficiaries, significant racial/ethnic differences exist in the diagnosis and treatment of depression. Vigorous clinical and public health initiatives are needed to address this persisting disparity in care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
77
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(82 citation statements)
references
References 70 publications
5
77
0
Order By: Relevance
“…15 For older African Americans, who comprise one of the fastest-growing minorities, depression and diabetes are diagnosed at more advanced stages compared to whites, when outcomes are less promising and care is more costly. 15,30,31 These facts necessitate novel culturally appropriate interventions to treat depression and improve diabetes self-management in this population.…”
Section: Discussionmentioning
confidence: 99%
“…15 For older African Americans, who comprise one of the fastest-growing minorities, depression and diabetes are diagnosed at more advanced stages compared to whites, when outcomes are less promising and care is more costly. 15,30,31 These facts necessitate novel culturally appropriate interventions to treat depression and improve diabetes self-management in this population.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, it appears that other key features of the program model-such as NORC programs' being connected to existing service delivery systems, being led by a parent organization with paid professionals, garnering support from government grants and contracts, and explicitly emphasizing the provision of health and social services (Bedney et al, 2010;Ormond et al, 2004)-makes NORC programs especially well suited to accommodate the needs of more vulnerable older adults. Previous studies have found that many of the services more consistently provided by NORC programs are especially likely to benefit older adults with greatest needs, such as professional coordination of services (Peikes, Chen, Schore, & Brown, 2009), health education and promotion (Lorig & Holman, 2003), and mental health services (Akincigil et al, 2012). Group activities, which both NORC program and Villages consistently offered, are also likely to benefit more vulnerable older adults, such as those who are socially isolated (Findlay, 2003).…”
Section: Norc Programsmentioning
confidence: 99%
“…In the United States, black patients are less likely to be diagnosed with depression (4.2%) than white patients (6.4%) or Hispanics (7.2%). (Akincigil, Olfson et al 2012) Depressed blacks are less likely than whites to receive antidepressants (52.5% versus 68.7%), and are half as likely to receive any depression treatment. (Akincigil, Olfson et al 2012) Among patients with depression or an anxiety disorder, blacks (17%) and Hispanics (24%) are less likely than whites (34%) to receive “appropriate care.” (Young, Klap et al 2001) Among patients with any mood or anxiety disorder, blacks (45.2%) are less likely than whites (56.3%) and Hispanics (56.4%) to receive “minimally adequate care.”(Ault-Brutus 2012) Blacks (23.1%) and Hispanics (25.3%) are also less likely than whites (36.3%) to receive any mental health care.…”
Section: Introductionmentioning
confidence: 99%
“…(Akincigil, Olfson et al 2012) Depressed blacks are less likely than whites to receive antidepressants (52.5% versus 68.7%), and are half as likely to receive any depression treatment. (Akincigil, Olfson et al 2012) Among patients with depression or an anxiety disorder, blacks (17%) and Hispanics (24%) are less likely than whites (34%) to receive “appropriate care.” (Young, Klap et al 2001) Among patients with any mood or anxiety disorder, blacks (45.2%) are less likely than whites (56.3%) and Hispanics (56.4%) to receive “minimally adequate care.”(Ault-Brutus 2012) Blacks (23.1%) and Hispanics (25.3%) are also less likely than whites (36.3%) to receive any mental health care. (Ault-Brutus 2012) In a study that included patients with a major depressive episode, panic disorder, generalized anxiety disorder, or another serious mental illness, blacks were less likely than whites to receive “guideline consistent care.” (Wang, Berglund et al 2000) Blacks (33.2%) were also less likely than whites (54%) to receive follow up after hospitalization for any mental illness.…”
Section: Introductionmentioning
confidence: 99%